How the Membranes Fuse: From Spontaneous to Induced. Issue 7 (14th May 2019) - Lu, Teng; Guo, Hongxia
Abstract: Membrane fusion not only involves many biologic phenomena such as neurotransmission, exo‐ and endocytosis, fertilization, membrane traffic, and viral infection, but also is relevant for many technological applications, that is, drug delivery. Therefore, unraveling the molecular mechanism of these important processes are both helpful to deepen the understanding of vital phenomena and instructive for the development of medical technology, for example, gene therapy. With the advances in computation power and algorithms, molecular simulation has become an invaluable tool to systematically investigate the entire membrane fusion process at the molecular level, in which not only the conformations and motions of lipid molecule but also the protein/DNA intermediates can easily be monitored. Nowadays, by these powerful methods, both the different pathways and the intermediate structures are discriminated, and the precise mechanisms and possible factors are explored. The present progress report reviews recent studies based on computational approaches with an aim to clarify the membrane fusion dynamics at a molecular level, which not only provides a useful starting point for a more thorough understanding about the membrane fusion process but also inspires developing promising applications such as drug or imaging‐agent delivery and gene therapy. Abstract : The present progress report reviews recent studies based on computational approaches with an aim to clarify the membrane fusion dynamics at a molecular level, which not only provides a useful starting point for a more thorough understanding about the membrane fusion process but also inspires developing promising applications .